Blockade Effects of Anti-Interferon- (IFN-) γ Autoantibodies on IFN-γ-Regulated Antimicrobial Immunity. (30th May 2019) - Krisnawati, Dyah Ika; Liu, Yung-Ching; Lee, Yuarn-Jang; Wang, Yun-Ting; Chen, Chia-Ling; Tseng, Po-Chun; Shen, Ting-Jing; Lin, Chiou-Feng
Abstract : The interferon- (IFN-) γ expression is elicited in response to microbial infections and activates immune surveillance by antimicrobial immune elements to induce microbial killing. Patients with adult-onset immunodeficiency who suffer from recurrent infections with microbes, particularly nontuberculous mycobacteria (NTM), commonly display genetic defects in IFN- γ signaling as well as the generation of anti-IFN- γ autoantibodies (autoAbs). Because IFN- γ is an activator of macrophage differentiation and a proinflammatory activator of innate immunity, the blockade effects of the autoAbs present in NTM patient serum on IFN- γ are hypothesized to regulate the antimicrobial function of macrophages. In the presence of patient serum, IFN- γ -induced type 1 macrophage (M1) differentiation was inhibited in PMA-stimulated human monocytic THP-1 cells. Treatment with patient serum significantly blocked the production of proinflammatory factors, including cytokines/chemokines and reactive oxygen/nitrogen species, by M1 macrophages. Importantly, IFN- γ -facilitated phagocytosis and degradation of heat-killed mycobacterium were decreased by cotreatment with patient serum. These results show the blockade activity of anti-IFN- γ autoAbs on IFN- γ -mediated antimicrobial immunity in macrophages.